2016
DOI: 10.1080/14328917.2016.1199134
|View full text |Cite
|
Sign up to set email alerts
|

Third order nonlinear optical properties and crystal structures of (E)-1 (3,4-dimethoxyphenyl)-3-(4-(trifluoromethyl)phenyl)prop-2-en-1-one

Abstract: A new organic material (E)-1-(3,4-dimethoxyphenyl)-3-(4-(trifluoromethyl)phenyl)prop-2-en-1-one (DPTF), belonging to chalcone family, exhibiting third-order non-linear optical properties has been synthesised and grown as single crystals, by slow evaporation technique at room temperature. The grown crystal was subjected to single-crystal X-ray diffraction analysis in order to establish their crystal structure. The DPTF crystal belongs to the triclinic crystal system (a = 8.0368 Å, b = 10.4345 Å, c = 10.4560 Å a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…By comparing the observed NLO parameters for both compounds, it is observed that 2PANC has a slightly higher nonlinearity than 3PANC experimentally, while it was found to be similar from computational studies. In this case, the higher value of 2PANC depends on the bearing of intermolecular interactions (C–H···N–C) that connect the inversion-related molecules into a side-by-side pattern, , and it is absent in 3PANC .…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the observed NLO parameters for both compounds, it is observed that 2PANC has a slightly higher nonlinearity than 3PANC experimentally, while it was found to be similar from computational studies. In this case, the higher value of 2PANC depends on the bearing of intermolecular interactions (C–H···N–C) that connect the inversion-related molecules into a side-by-side pattern, , and it is absent in 3PANC .…”
Section: Resultsmentioning
confidence: 99%